Investigation of Ho ion production with a laser ablation ion source. Issue 1 (1st April 2022) - Bhandari, R.; Horana Gamage, M.; Gamage, N. D.; Redshaw, M.
Abstract: At Central Michigan University (CMU), we are developing the CMU High Precision Penning Trap (CHIP-TRAP) with the aim of performing high-precision mass measurements on stable and long-lived radioactive isotopes. A major goal of CHIP-TRAP is to measure the 163 Ho EC Q value to ∼1 eV precision to aid direct neutrino mass determination experiments with 163 Ho. CHIP-TRAP utilizes a laser ablation source (LAS) and a Penning ion trap source to produce ions from solid and gaseous samples, respectively. Ions from these sources are identified by measuring their times-of-flight from the source to their detection on a micro channel plate detector (MCP). With the goal of producing 163 Ho+ ions from a solution of 163 Ho dissolved in nitric acid and dried out on a backing target to be inserted into the LAS, we investigated the production of naturally occurring, stable 165 Ho+ following this method. We aimed to determine the minimum number of Ho atoms required on the target to produce a detectable number of Ho + ions, and to investigate different backing materials to determine if a particular material minimized contaminant ions from the backing material and maximized the number of Ho + ions compared to, for example, HoO + ions.